Stakeholder knowledge and perceptions of the circular economy in Ugandan cities - Geme, Tom; Nijman, Elke; Ntawuhiganayo, Elisée Bahati; Negesa, Doryn (Frontiers in Sustainability, 2023)
Transitioning to a circular economy (CE) has been touted as the necessary paradigm shift to counterbalance the ever-increasing socio-economic metabolism in the face of global challenges such as climate change, biodiversity loss, population growth, pollution, and unemployment. Previous research has indicated that the transition to CE requires stakeholder collaboration. Yet, at present, a dearth of literature exists about stakeholder knowledge and perceptions of CE, more so in Africa. This begs the question; how will stakeholders collaborate when their understanding of the subject is dissimilar? To contribute to closing this knowledge gap, this research employs a mixed-methods approach to investigate the knowledge and perception of CE among key stakeholders in selected cities in Uganda. Interview data from 230 respondents selected via a snowballing process in the Ugandan cities of Gulu, Jinja, Masaka, Mbale, Mbarara and the Greater Kampala Metropolitan Area indicate that several stakeholder groups are involved in Uganda’s CE space. These include government, businesses, civil society, the public as well as academia, research and think tanks. In terms of CE knowledge, the findings show that respondents were generally knowledgeable about CE. However, much of the knowledge is about the 3Rs (reduce, repair and recycle) and waste management to the point that many respondents misconstrued recycling as synonymous with CE. Overall, participant knowledge and perception of CE are determined by the level of education, sector of operation, position at the workplace, how long one has been in the CE space and whether one participated in decision-making. The findings indicate that respondents believe that the government had not done enough in promoting CE concepts and practices including creating avenues for stakeholder collaboration. The findings offer insights for CE proponents on attributes to consider when advocating and communicating about CE. This research could also inform the formulation of policies that stimulate CE development, particularly in determining entry points for CE interventions and effective stakeholder engagement.